How youth engage in online deliberation: an empirical study based on individual psychological motivations from China - Lin, Yuyang; Tan, Yunpeng; Wang, Xiao; Liang, Zhenwei (Frontiers in Psychology, 2025)
Clarifying the youth expression patterns on the internet and guiding contemporary youth to participate in public deliberation in an orderly manner within the online society will contribute to their growth and development and further promote the democratic development of society. While many studies have explored the impact of structural factors in the online environment on public deliberation, they overlook the psychological processes of the participants themselves. This paper, based on the background of social conflict events, focuses on the online public deliberation behavior of young people and explores how the involvement and inter-group emotional contagion influence the level of online public deliberation from the perspective of individual psychological motivations, as well as the mediating role of selective exposure. Through a questionnaire survey (n = 1,092), this study found that involvement has a positive impact on the level of online public deliberation, but similar to inter-group emotional contagion, it can lead to a higher degree of conversational dominance. Inter-group emotional contagion is not conducive to deliberation. Selective exposure serves as an important mediator between individual cognition and emotion and online public deliberation. The research findings examine the influence pathways of individual cognition on online public deliberation, providing insights for understanding the mechanisms of youth online expression and enhancing the degree of online public deliberation.